2018
DOI: 10.3855/jidc.10381
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Human Herpesvirus 8 antibodies affect both insulin and glucose uptake by virus-infected human endothelial cells

Abstract: Introduction: Human Herpesvirus 8 (HHV8) is known to be the cause of the malignant tumour named Kaposi's sarcoma. It is believed to induce an intense modification of cell metabolism in endothelial cells. In this work we analysed the role of anti-HHV8 antibodies in both the insulin and glucose uptake of HHV8-infected primary human endothelial cells (HUVEC). Methodology: Western blotting, immunofluorescence and radiolabelled glucose were employed to assess the pPI3K expression, insulin binding and glucose-uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Surprisingly, they also discovered that anti-HHV8 antibodies could selectively induce a further increase in insulin and glucose uptake in the latent HHV8-infection. These authors finally suggested that the immune response to HHV8-infection was able to stimulate cell metabolism by inducing an increased insulin and glucose uptake in virus infected cells, as generally happens in several tumour-viral infections [24]. As a matter of fact, when anti-HHV8 antibodies were added to endothelial cells during HHV8 latent infection, a further increase in pPI3K expression and in insulin and glucose uptake was observed.…”
Section: Immune Response and Cell Metabolismmentioning
confidence: 84%
See 4 more Smart Citations
“…Surprisingly, they also discovered that anti-HHV8 antibodies could selectively induce a further increase in insulin and glucose uptake in the latent HHV8-infection. These authors finally suggested that the immune response to HHV8-infection was able to stimulate cell metabolism by inducing an increased insulin and glucose uptake in virus infected cells, as generally happens in several tumour-viral infections [24]. As a matter of fact, when anti-HHV8 antibodies were added to endothelial cells during HHV8 latent infection, a further increase in pPI3K expression and in insulin and glucose uptake was observed.…”
Section: Immune Response and Cell Metabolismmentioning
confidence: 84%
“…In addition, some sulfonamide drugs have recently been shown to be able to interfere with the binding of LANA to the cellular DNA [23]. It is worth noting that several other DNA (e.g., Adenoviruses and Herpesviruses) and RNA (e.g., Rubella, Dengue virus, Enteroviruses, Hepatitis C virus and HIV) viruses were found to be able to affect the host's metabolism favouring not only the onset of tumours but also some other chronic diseases, namely metabolic syndrome and diabetes [4,[24][25][26][27][28][29].…”
Section: Virology and Molecular Biology Of Hhv8mentioning
confidence: 99%
See 3 more Smart Citations